Resilient Regional Labour Markets as Triggers of Innovation Success during Crises: Perspective of EU Innovation Leaders - Fišera Tomáš; Vaníček Bernard (TalTech Journal of European Studies)
Despite the growing interest in the impact of economic crises on regional labour markets, innovation, and regional resilience, the relationship between these economic aspects remains under-researched in the context of these crises. This research aims to fill this gap by investigating how regional labour markets affect the innovation success of European Union countries. We focus on analysing the impact of female and youth unemployment, labour costs, and hours worked on the innovation success of 22 European Union countries over the period 2013–2021, with a special focus on countries identified as innovation leaders in the European Union. Using regression analysis, we find that higher female unemployment and lower hours worked have a positive effect on innovation success. Higher labour costs then have a negative impact on innovation success in the European Union but are not significant for the innovation leaders’ success, providing new insights into the complex relationship between the labour market and innovation success. Through a Difference-in-Differences analysis, we additionally demonstrate that there is a causal effect, revealing a greater decline in innovation success among innovation leaders with the advent of the COVID-19 pandemic compared to the remaining (control) 18 European states. The study further highlights the critical role of targeted social and employment policies in enhancing innovation performance, emphasising the need for tailored strategies to support vulnerable labour market groups, and provides directions for future research to explore these dynamics in greater depth.